Structural integrity analysis of an Ignalina nuclear power plant building subjected to an airplane crash - Dundulis, Gintautas; Kulak, Ronald F.; Marchertas, Algirdas; Uspuras, Eugenijus (Nuclear engineering and design, 2007)
Recent terrorist attacks using commandeered commercial airliners on civil structures have raised the issue of the ability of nuclear power plants to survive the consequences of an airliner crash. The structural integrity analysis due to the effects of an aircraft crash on an Ignalina nuclear power plant (INPP) accident localization system (ALS) building is the subject of this paper. A combination of the finite element method and empirical relationships were used for the analysis. A global structural integrity analysis was performed for a portion of the ALS building using the dynamic loading from an aircraft crash impact model. The local effects caused by impact of the aircraft's engine on the building wall were evaluated independently by using an empirical formula. The results from the crash analysis of a twin engine commercial aircraft show that the impacted reinforced concrete wall of the ALS building will not have through-the-wall concrete failure, and the reinforcement will not fail. Strain-rate effects were found to delay the onset of cracking. Therefore, the structural integrity of the impacted wall of the INPP ALS building will be maintained during the crash event studied.